First in‐human experience with a novel robotic platform and Magnetic Surgery System. Issue 1 (26th September 2020) - Barajas‐Gamboa, Juan S.; Huidobro, Felipe; Jensen, Joaquin; Luengas, Rafael; Rodriguez, John; Abril, Carlos; Corcelles, Ricard; Kroh, Matthew
Abstract: Background: Magnetic technologies have been introduced to reduce invasiveness of surgical procedures. This study was aimed to analyse the performance of a novel combined magnetic‐robotic controller as an enhanced accessory to the Magnetic Surgical System in laparoscopic cholecystectomy (LC). Methods: This was a prospective study of 10 consecutive patients undergoing LC with this novel surgical system. Results: Ten patients were included, nine were female. The mean age was 30.3 ± 9 years. All patients had chronic cholecystitis. Procedures were completed successfully. The median operative time was 50 ± 11 min. The system performed effectively in all cases with no need of additional interventions. There were no device‐related complications or side effects. All patients were discharged the same day. Recovery was uneventful during follow‐up. Conclusions: This study demonstrates the first in‐human successful performance of surgeries utilizing a novel combination of magnetic and robotic technologies in one integrated system.